A dose escalation study to evaluate the safety of an aerosol BCG infection in previously BCG-vaccinated healthy human UK adults - Fredsgaard-Jones, Timothy; Harris, Stephanie A.; Morrison, Hazel; Ateere, Alberta; Nassanga, Beatrice; Ramon, Raquel Lopez; Mitton, Celia; Fletcher, Eve; Decker, Jonathan; Preston-Jones, Hannah; Jackson, Susan; Mawer, Andrew; et al. (Frontiers in Immunology, 2024)
Tuberculosis (TB) is the leading cause of death worldwide from a single infectious agent. Bacille-Calmette Guerin (BCG), the only licensed vaccine, provides limited protection. Controlled human infection models (CHIMs) are useful in accelerating vaccine development for pathogens with no correlates of protection, however the need for prolonged treatment makes Mycobacterium tuberculosis an unethical challenge agent. Aerosolised BCG provides a potential safe surrogate of infection. A CHIM in BCG-vaccinated, as well as BCG-naïve individuals would allow identification of novel BCG-booster vaccine candidates and facilitate CHIM studies in populations with high TB endemicity. The purpose of this study was to evaluate the safety and utility of an aerosol BCG CHIM in historically BCG-vaccinated volunteers.Twelve healthy, historically BCG-vaccinated UK adults were sequentially enrolled into dose-escalating groups. The first three received 1x10 4 cfu aerosol BCG Danish 1331 via nebuliser. After safety review, subsequent groups received doses of 1x10 5 cfu, 1x10 6 cfu or 1x10 7 cfu. Safety was monitored through self-reported adverse events (AEs), laboratory tests, and lung function testing. Immunology blood samples were taken pre-infection and at multiple timepoints post-infection. A bronchoalveolar lavage (BAL) taken fourteen days post-infection was analysed for presence of live BCG.No serious AEs occurred during the study. Solicited systemic and respiratory AEs were frequent in all groups, but generally short-lived and mild in severity. There was a trend for more reported AEs in the highest dose group. No live BCG was detected in BAL from any volunteers. Aerosol BCG induced potent systemic cellular immune responses in the highest dose group seven days post-infection.Aerosol BCG infection up to a dose of 1x10 7 cfu was well-tolerated in historically BCG-vaccinated healthy, UK adults. No live BCG was detected in the BAL fluid fourteen days post-infection despite potent systemic responses, suggesting early clearance. Further work is needed to expand the number of volunteers receiving BCG via the aerosol route to refine and establish utility of this aerosol BCG CHIM.